Certain Indefinite Integrals Involving Lucas Polynomials and Harmonic Number (Global Journal of Science Frontier Research, 2012)
In this paper we have established certain indefinite integrals involving Harmonic number and Lucas Polynomials. The results represent here are assume to be new.
Keywords: Polylogarithm; Lucas polynomials; Harmonic Number; Gaussian Hypergeometric Function